German Language Acquisition of Refugee Children—The Role of Preschools and Language Instruction - Seuring, Julian; Will, Gisela (Frontiers in Sociology, 2022)
Mastering the language of the destination country is key to immigrant and refugee children’s educational success. Refugee children typically face the challenge of starting or continuing their educational carrier in a completely new context and in a completely new language. In this study, we examine the role of preschool attendance and formal language instruction in supporting young refugee children to acquire destination language competencies. We pursue three research objectives: First, we aim at identifying relevant conditions associated with German language acquisition in general. Second, we examine the (relative) importance of institutional learning support in preschool and language instruction. Third, we investigate whether the benefits of attending preschool are more pronounced for refugee children who have only limited exposure to the destination language outside of the institutional context, as compared to children who have more exposure to the language outside of preschool. Using data from the ReGES study, we analyze the early processes of destination language acquisition among a large population of refugee children of preschool age in Germany. Our findings indicate that conditions associated with motivation, exposure and efficiency of learning that were found in prior research to determine destination language competencies of children from other immigrant groups apply to refugee children in a similar manner. Additional conditions associated with the specific circumstances that refugees often experience, including possible consequences of insecure residence status, risk of post-traumatic stress disorders, and living in collective accommodation, do not significantly contribute to this outcome in our analysis. Furthermore, we find that there is a positive relationship between children’s German language competency levels and both preschool attendance and formal language instruction. The findings indicate that the benefits of attending preschool are largely related to additional language instruction that refugee children receive within this context. Moreover these benefits are particularly pronounced among refugee children who have only limited exposure to German at home and in their everyday lives. Overall, our findings emphasize the importance of preschool attendance and formal language instruction for refugee children’s destination language acquisition.